Biomedical Chemistry. Current Trends and Developments - Vale, Nuno (De Gruyter, 2016)
Biomedical Chemistry provides readers with an understanding of how fundamental chemical concepts are used to combat some diseases. The authors explain the interdisciplinary relationship of chemistry with biology, physics, pharmacy and medicine. The results of chemical research can be applied to understand chemical processes in cells and in the body, and new methods for drug transportation. Also, basic chemical ideas and determination of disease etiology are approached by developing techniques to ensure optimum interaction between drugs and human cells. This Book is an excellent resource for students and researchers in health-related fields with frontier topics in medicinal and pharmaceutical chemistry, organic chemistry and biochemistry.